Gold Nanoclusters for Bacterial Detection and Infection Therapy - Tang, Mingxiu; Zhang, Jian; Yang, Chunyan; Zheng, Youkun; Jiang, Hui (Frontiers in Chemistry, 2020)
Infections caused by antibiotic-resistant bacteria have become one of the most serious global public health crises. Early detection and effective treatment can effectively prevent deterioration and further spreading of the bacterial infections. Therefore, there is an urgent need for time-saving diagnosis as well as therapeutically potent therapy approaches. Development of nanomedicine has provided more choices for detection and therapy of bacterial infections. Ultrasmall gold nanoclusters (Au NCs) are emerging as potential antibacterial agents and have drawn intense attention in the biomedical fields owing to their excellent biocompatibility and unusual physicochemical properties. Recent significant efforts have shown that these versatile Au NCs also have great application potential in the selective detection of bacteria and infection treatment. In this review, we will provide an overview of research progress on the development of versatile Au NCs for bacterial detection and infection treatment, and the mechanisms of action of designed diagnostic and therapeutic agents will be highlighted. Based on these cases, we have briefly discussed the current issues and perspective of Au NCs for bacterial detection and infection treatment applications.